Le gouvernement des corps séropositifs. Dynamique de pénalisation de la transmission sexuelle du VIH - Charlotte Pezeril (Genre, Sexualité et Société)
This article aims at understanding he wave of criminalization of sexual transmission of HIV, since the early 2000s, in many countries (including Canada, Britain, France and Belgium), when HIV became a chronic diseases through effective antiretroviral treatments. In order to capture more accurately the links between the global and the local use of the law and the mobilizations it entails, this article presents an ethnographic analysis of the trial of Huy, which is the first conviction for sexual transmission of HIV in Belgium in 2011. This trial shows how gender relations, "race" and class structure exchanges, making intersectional analysis unavoidable, and how it ultimately constitutes a "government of HIV-positive body" based on a new serological responsibility.